PENGARUH KONFLIK TERHADAP KINERJA ORGANISASI / PERUSAHAAN - Lies Indriyatni (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2010)
A Conflict is a process began from someone’s assumption to certain person which later on can lead to a problem. The factors that can trigger a conflict can be classified into 3 categories, which are communication, structure and individual. The impact of a conflict on the organization or company performance can be seen according to the kind of the conflict itself. There are two kinds of conflict:-          Functional Conflicts are All kind of conflict that can support organization or company’s main objective in improving their performance, In other hand-          Dysfunctional Conflicts are all kind of conflict that may obstruct and block an organization or  a company in improving its performance.Because of the explanation above, a manager’s duty is on how he can recognize the conflicts so well that he can manage them so the conflict become beneficial for the performance improvement of the company or organization.